2021
DOI: 10.1108/ijse-07-2020-0474
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and adoption of positive selection technology among yam farmers in West Africa

Abstract: PurposeThis paper aims to investigate how awareness influences the adoption of positive selection (PS) technology among smallholder yam farmers in West Africa. PS has the potential of increasing yield and reducing disease incidence and severity in yam production.Design/methodology/approachThis paper applies the average treatment effect (ATE) methodology to estimate the rates of awareness and adoption of the PS technology and associated factors using data from 678 smallholder seed yam farmers in Ghana and Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…In addition, farmers are able to appreciate the importance of these practices and better understand them during dissemination techniques by extension agents and other sources. The result are similar to the findings (Enrique and Eduardo, 2006;Alhassan et al, 2018;Baiyegunhi et al, 2019;Barnes et al, 2019;Kondo et al, 2020;Asante et al, 2021), where positive effects were found with education and adoption of improved technologies.…”
Section: Adoption Of Improved Nursery Practices Of Tomato Productionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, farmers are able to appreciate the importance of these practices and better understand them during dissemination techniques by extension agents and other sources. The result are similar to the findings (Enrique and Eduardo, 2006;Alhassan et al, 2018;Baiyegunhi et al, 2019;Barnes et al, 2019;Kondo et al, 2020;Asante et al, 2021), where positive effects were found with education and adoption of improved technologies.…”
Section: Adoption Of Improved Nursery Practices Of Tomato Productionsupporting
confidence: 91%
“…Extension visits positively and significantly influenced the adoption of fertilizer application and hardening practices; thus, farmers are more likely to adopt these practices and other improved production practices through advice and guidance obtained from extension agents. Consistent with previous studies (Ayandiji and Adeniyi, 2011;Simtowe et al, 2016;Asante et al, 2017;Alhassan et al, 2018;Asante et al, 2021; extension has been found to positively influence the adoption of improved crop production technologies. Farmers are more likely to access to staking information and best staking times through FBO membership.…”
Section: Adoption Of Improved Nursery Practices Of Tomato Productionsupporting
confidence: 91%